An analysis about educational philosophies (Research, Society and Development, 2021)
The approached content has as its main foundation to analyze an educational philosophy, especially with regard to philosophical approaches. In this perspective, this article, through exploratory research, of a qualitative nature, deductive method, collection of bibliographic data, proceeded in order to carry out an analysis about the educational philosophical lines currently adopted by teachers with the styles of effective teaching in the daily life of the school. classroom. Nevertheless, they were imputed to the criteria adopted by the “Evaluation of Philosophical Preferences”, which was developed by Wiles and Bondi (2007) and adapted by Doğanay and Sari (2003), categorizing into five educational philosophies, being perennialism, idealism, realism, experimentalism and existentialism. Finally, in view of the exposed problem, it was sought to elucidate the need for continuity of philosophical study, based on social promotion and social well-being, to outline mechanisms capable of preserving and guaranteeing the fundamental right to education, in view of the substantial disadvantages harmed to the Democratic State of Law for non-observance of this guarantee.